1980
DOI: 10.1007/bf01804978
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of protein and non-protein amino acids on a clay mineral: A possible role of selection in chemical evolution

Abstract: The adsorption of protein and non-protein amino acids by Na-montmorillonite was studied at pH 3, 7, and 10, in order to determine whether clays could have played a part in selection of protein over non-protein amino acids in prebiotic times. Five pairs of amino acids, containing two to six carbons, were used at a concentration equal to 100% cation exchange capacity of the clay in adsorption experiments. The following pairs of protein and non-protein amino acids were used: glycine and sarcosine, alpha-alanine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1981
1981
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Friebele (1980) tried to evaluate if biological amino acids could have been selected from a mixture also containing their non-biological counterparts by adsorption on montmorillonite clays but came up with a negative answer.…”
Section: Adsorption Selectivitiesmentioning
confidence: 99%
“…Friebele (1980) tried to evaluate if biological amino acids could have been selected from a mixture also containing their non-biological counterparts by adsorption on montmorillonite clays but came up with a negative answer.…”
Section: Adsorption Selectivitiesmentioning
confidence: 99%
“…The main interest in silicon has not been as the backbone molecule of a life system, but its role as a surface adsorbent and catalyst for proper alignment and polymerization of polyadenines and polyuracils (Burton et al, 1974;Ding et al, 1996;Ertem and Ferris, 1996Ferris et al, 1996Ferris et al, , 1988Ferris et al, , 1989Ferris and Ertem, 1992;Friebele et al, 1980Friebele et al, , 1981Huang and Ferris, 2003;Kawamura and Ferris, 1999;Miyakawa and Ferris, 2003;Paecht-Horowitz and Eirich, 1988;Trevors, 1997a). But polyadenines and polyuracils, like the monotonous clay crystals to which they adsorb, contain almost no Shannon uncertainty (often misnamed ''information'').…”
Section: Astrobiological Considerationsmentioning
confidence: 99%
“…Indeed, in such systems, simple precursors such as sugars and amino acids, (among the most abundant constituents of living organisms), can combine under reducing as well as oxidizing conditions. In continental environments, the catalytic activity of the finest soil fractions, particularly clay minerals, in many chemical reactions is well documented, and some researchers even examined their possible role in the origin of life (Cairns Smith, 1966, 1974Friebele et aL, 1980). In particular, the catalytic activity of smectites for polymerization reactions of aromatic molecules has been studied by many authors (Mortland & Halloran, 1976;Sawhney et al, 1984;Wang et al, 1985;Wang & Huang, 1987;Zubkova, 1989;Wang, 1991), who suggested a catalytic role for clays.…”
mentioning
confidence: 99%